2008
DOI: 10.1038/sj.bjp.0707505
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid CB2 receptors in human brain inflammation

Abstract: The presence of functional cannabinoid CB 2 receptors in the CNS has provoked considerable controversy over the past few years. Formerly considered as an exclusively peripheral receptor, it is now accepted that it is also present in limited amounts and distinct locations in the brain of several animal species, including humans. Furthermore, the inducible nature of these receptors under neuroinflammatory conditions, in contrast to CB 1 , makes them attractive targets for the development of novel therapeutic app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
203
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(211 citation statements)
references
References 94 publications
4
203
0
4
Order By: Relevance
“…Furthermore, we were encouraged by the fact that transient transfection of receptors into ␤-arrestin-EA parental HEK293 cells gave robust signals, circumventing the need for labor-intensive stable cell line generation and selection. The EC 50 values obtained in the transient ␤-arrestin assay for a subset of receptors were significantly higher than the EC 50 values obtained from other assay formats (Table 1). This appears to be partly due to the low sensitivity resultant from transient transfection method.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…Furthermore, we were encouraged by the fact that transient transfection of receptors into ␤-arrestin-EA parental HEK293 cells gave robust signals, circumventing the need for labor-intensive stable cell line generation and selection. The EC 50 values obtained in the transient ␤-arrestin assay for a subset of receptors were significantly higher than the EC 50 values obtained from other assay formats (Table 1). This appears to be partly due to the low sensitivity resultant from transient transfection method.…”
Section: Resultsmentioning
confidence: 59%
“…Data Analysis-EC 50 or IC 50 values were obtained by fitting the data with the sigmoidal dose-response curve-fitting tool of the GraphPad Prism software. Eight or twelve different concentrations were usually used and two or three data points per concentration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Δ9-THC has antioxidant effects in α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid-and N-methyl-D-aspartate-mediated cytotoxicity models via a CB 1 R-independent mechanism [87]. Cannabinoids reduce neuronal and glial release of the proinflammatory cytokines tumor necrosis factor-α, NO, interleukin (IL)-1 and IL-6 [88][89][90][91][92][93], and increase release of anti-inflammatory cytokines IL-4, IL-10, and IL-1 receptor antagonist (IL-1a) [94,95] via CB1R-and CB2R-dependent mechanisms in neurons and glia [94,95] (reviewed in [96]). Δ9-THC also transiently activates and desensitizes the transient receptor potential (TRP) channels TRPA1, TRPV1, and TRPV2 [97][98][99].…”
Section: δ9-thcmentioning
confidence: 99%
“…It has been demonstrated that in microglia of AD patients, CB1 and CB2 receptor expression is significantly increased, while in basal ganglia and hippocampus neuronal CB1 receptor expression is decreased [58]. Therefore, endocannabinoid system might play an important role in AD pathogenesis [59].…”
Section: Medicine Medicine 2016;5(2):562-82 Endocannabinoid System Romentioning
confidence: 99%